Psychological distress and its influencing factors among psychiatric nurses in China: A cross-sectional study - Wang, Juan; Zheng, Zhongren; Tang, Yingxue; Zhang, Rui; Lu, Qinghua; Wang, Bin; Sun, Qihua (Frontiers in Psychiatry, 2022)
BACKGROUND: Psychiatric nurses often face abuse, attacks, escape, suicides, and other situations related to the care of patients with mental disorders, which are more likely to induce psychological distress. AIMS: This study aimed to examine the relationship between coping styles and psychological distress among Chinese psychiatric nurses in Shandong and the significance of sleep quality as a mediating factor. METHODS: A total of 812 psychiatric nurses in Shandong, China, were investigated using the Psychological Distress Scale (K10), Simplified Coping Style Questionnaire (SCSQ), Pittsburgh Sleep Quality Index (PSQI) and self-compiled general information questionnaire. RESULTS: Psychological distress was detected in 571 psychiatric nurses (70.3%). The psychological distress of psychiatric nurses was significantly different with respect to professional title (X2 = 10.627, P < 0.05) and shift work (X2 = 9.120, P < 0.01). Psychological distress positively correlated with negative coping style (r = 0.266, P < 0.01) and sleep quality (PSQIT) (r = 0.532, P < 0.01). A significant positive correlation was found between psychological distress and all dimensions of sleep quality (r = 0.158-0.456, P < 0.05). Professional title, positive coping style, negative coping style, sleep quality (PSQIT), subjective sleep quality, sleep disorder and daytime dysfunction predicted psychological distress in psychiatric nurses (R2 = 0.363, F = 65.343, P < 0.01). The relationship between negative coping style and psychological distress was partially mediated by sleep quality, with the mediating effect accounting for 37.97% of the total effect. CONCLUSIONS: Psychiatric nurses have a high rate of psychological distress, which is closely related to coping styles, and sleep quality has a certain regulatory effect.